Lucy as A ‘Rising Character’: Character Analysis of Lucy Snowe of Charlotte Brontë’s Villette - Aruna (Cultural Arts Research and Development, 2022)
In Villette, Charlotte Brontë portrays a woman’s growth in an incredibly subtle way. Her heroine goes through a lonely and painful process from awakening to transformation. Lucy Snowe possess inner strength and she rises out of difficult circumstances — suffering, seeking, surviving and finding her career. Charlotte’s insights about love,career, marriage and life are more matured compared to her previous novels , she also presents her deeper concern and reflection on Victorian women’s situation in the novel. Inspired by Lucy Snowe’s spirit, this paper briefly analyses her sterling character and how she rises from an unrecognized woman to a respected teacher.